CD9+ Regulatory B Cells Induce T Cell Apoptosis via IL-10 and Are Reduced in Severe Asthmatic Patients - Brosseau, Carole; Durand, Maxim; Colas, Luc; Durand, Eugénie; Foureau, Aurore; Cheminant, Marie-Aude; Bouchaud, Gregory; Castan, Laure; Klein, Martin; Magnan, Antoine; Brouard, Sophie (Frontiers in Immunology, 2018)
CD9 was recently identified as a marker of murine IL-10-competent regulatory B cells. Functional impairments or defects in CD9+ IL-10-secreting regulatory B cells are associated with enhanced asthma-like inflammation and airway hyperresponsiveness. In mouse models, all asthma-related features can be abrogated by CD9+ B cell adoptive transfer. We aimed herein to decipher the profiles, features and molecular mechanisms of the regulatory properties of CD9+ B cells in human and mouse. The profile of CD9+ B cells was analyzed using blood from severe asthmatic patients and normal and asthmatic mice by flow cytometry. The regulatory effects of mouse CD9+ B cells on effector T cell death, cell cycle arrest, apoptosis and mitochondrial depolarization were determined using yellow dye, propidium iodide, Annexin V and JC-1 staining. MAPK phosphorylation was analyzed by western blotting. Patients with severe asthma and asthmatic mice both harbored less CD19+CD9+ B cells, although these cells displayed no defect in their capacity to induce T cell apoptosis. Molecular mechanisms of regulation of CD9+ B cells characterized in mouse showed that they induced effector T cell cycle arrest in sub G0/G1, leading to apoptosis in an IL-10-dependent manner. This process occurred through MAPK phosphorylation and activation of both the intrinsic and extrinsic pathways. This study characterizes the molecular mechanisms underlying the regulation of CD9+ B cells to induce effector T cell apoptosis in mice and humans via IL-10 secretion. Defects in CD9+ B cells in blood from patients with severe asthma reveal new insights into the lack of regulation of inflammation in these patients.